2005
DOI: 10.2164/jandrol.05063
|View full text |Cite
|
Sign up to set email alerts
|

DNA Integrity Is Compromised in Protamine‐Deficient Human Sperm

Abstract: ABSTRACT:The objective of this study was to examine the relationship between DNA integrity and protamines in human sperm. One hundred forty-nine male infertility patients were included in an Institutional Review Board-approved study. Sperm were evaluated for DNA fragmentation using the DNA Integrity Assay, a test equivalent to the sperm chromatin structure assay (SCSA). Additionally, nuclear proteins were extracted and the protamine-1/protamine-2 ratio (P1/ P2), protamine-1 (P1), protamine-2 (P2), and total pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
152
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(169 citation statements)
references
References 43 publications
11
152
1
5
Order By: Relevance
“…The indirect association between abnormal protamine expression and severely altered spermatogenesis may not be intuitively obvious, but animal studies have also shown that spermatogenesis is severely altered when protamine expression is experimentally reduced [Zhong et al 1999;Aoki et al 2005]. In contrast to human data, haploinsufficient mice show a homogenous population of severely affected sperm, while infertile male patients with protamine deregulation exhibit a truly heterogenous population of sperm [Cho et al 2001;Aoki et al 2005;Aoki et al 2006b;Zhang et al 2006]. This may be due to focal disruptions in the tubular structure of the testis or disruption of upstream regulators with an incomplete phenotypic penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…The indirect association between abnormal protamine expression and severely altered spermatogenesis may not be intuitively obvious, but animal studies have also shown that spermatogenesis is severely altered when protamine expression is experimentally reduced [Zhong et al 1999;Aoki et al 2005]. In contrast to human data, haploinsufficient mice show a homogenous population of severely affected sperm, while infertile male patients with protamine deregulation exhibit a truly heterogenous population of sperm [Cho et al 2001;Aoki et al 2005;Aoki et al 2006b;Zhang et al 2006]. This may be due to focal disruptions in the tubular structure of the testis or disruption of upstream regulators with an incomplete phenotypic penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…gonadotoxins, hyperthermia, oxidants, endocrine abnormalities) [2][3][4][5][6][7][8][9][10]. Investigators have suggested that protamine deficiency (with aberrant chromatin remodeling), reactive oxygen species (ROS) and abortive apoptosis may cause sperm DNA damage [11][12][13][14][15][16][17][18]. De Iuliis et al, have proposed a two-step model to explain the origin of sperm DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Longtemps considéré comme un simple tuyau, l'épididyme apparaît clairement maintenant comme un tissu essentiel à la fertilité mâle. Les phénomènes mis en exergue ici trouvent leur écho en clinique, comme en témoigne une littérature pléthorique qui atteste qu'une fraction importante des infertilités mâles est corrélée à des dommages oxydants des spermatozoïdes affectant la mobilité progressive, perturbant la capacité à réaliser la réaction acrosomique et conduisant à un niveau élevé de fragmentation nucléaire [24][25][26][27][28][29][30][31][32][33][34][35][36][37] …”
Section: Discussionunclassified